2023
DOI: 10.2147/ijnrd.s403699
|View full text |Cite
|
Sign up to set email alerts
|

Can Oral Zinc Supplementation Reduce Relapses in Childhood Steroid-Sensitive Nephrotic Syndrome? A Systematic Review

Abstract: Introduction Frequent relapses and steroid dependence are common treatment challenges of steroid-sensitive nephrotic syndrome (SSNS) in children. Acute respiratory infection (ARI) is the most frequently reported trigger of relapse. Given the role of zinc supplementation in preventing ARI, some studies show that this targeted intervention may reduce relapses in childhood SSNS. Aim This systematic review aimed to determine if oral zinc supplementation can significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nephrotic syndrome can recur, and the main triggers are acute respiratory infections, UTIs, diarrhea, peritonitis, and skin infections [ 192 , 193 , 194 , 195 , 196 ]. In pediatric patients, low zinc levels have been found during remission or relapse of nephrotic syndrome, regardless of serum albumin levels, probably due to urinary losses [ 197 ]. Given its well-established role in preventing acute respiratory infections, studies have suggested that zinc supplementation may reduce relapses in children with NS and promote prolonged remission [ 198 ] ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotic syndrome can recur, and the main triggers are acute respiratory infections, UTIs, diarrhea, peritonitis, and skin infections [ 192 , 193 , 194 , 195 , 196 ]. In pediatric patients, low zinc levels have been found during remission or relapse of nephrotic syndrome, regardless of serum albumin levels, probably due to urinary losses [ 197 ]. Given its well-established role in preventing acute respiratory infections, studies have suggested that zinc supplementation may reduce relapses in children with NS and promote prolonged remission [ 198 ] ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%